METAPHORICAL EXPRESSION USED IN POEMS ON POETRYANDGAHWA’S INSTAGRAM - Afdilla . Moulidya (LINGUISTIK TERAPAN, 2023)
Metaphor is an interesting way to convey meaning in literary works. It is considered a language art because of its wide range of diction and distinct style. This study will be conducted as a qualitative study with a descriptive design. In this case, the researcher used the metaphor theory of Parera (2004) and theory discourse analysis of Michael Foucault (2017) to describe the types of metaphor were found in poems, to examine the realization of the metaphor in poems on Poetryandgahwa’s Instagram account and to investigate resistances through discursive formations in archeological method by Foucault. From the poems entitled “A conversation with a flower, Candle, Show me, The moon in your eyes, You and every pretty thing, Every Tongue Said, When your heart refused to beat, Summer rain, Rupture in the cloud, and What guides my pen” consists of 21 lines that used metaphor. The resultd of the study shown that metaphor expression used anthropomorphic metaphor, and it got the highest percentages. Then, it consist of two resistances there are: resistances in transmission and resistances in condition.